Hooway for Wodney Wat - Lester, Helen; Munsinger, Lynn (New York. : Houghton Mifflin, 1999)
All his classmates make fun of Rodney because he can't pronounce his name, but it is Rodney's speech impediment that drives away the class bully.
Keywords: Speech disorders; Schools; Bullies; Rodents